CONTEMPORARY POPULISM AND THE ECONOMIC CRISIS IN WESTERN EUROPE - Poli, Maria Daniela (Baltic Journal of Political Science, 2017)
Given a threatening new wave of populism crossing Europe, this article examines the link between populism and crisis as a Gordian knot and explores the relationship between contemporary populism and the Great Recession in Western Europe by underscoring how the principal feature of this relationship is the perception of the European Union as a common enemy.